General Geology of Lawin Area along Grik – Lawin Transect with Emphasis on Sedimentology of Tertiary Sedimentary Basin - Mazlan, Mohamad Hisham (Universiti Teknologi PETRONAS, 2014)
This project is about geological study in Lawin, Gerik, Perak. The study would be divided into two part in which on the first part it is a general geology study where the final result would be rose diagrams, stereonet and geological map with its cross section along the transect line. Then the study will emphasize more on sedimentology of the Lawin Tertiary Sedimentary Basin and the end product would be from petrography, sedimentary log, and XRF. All the results then further discussed and concluded. Future study should be done to evaluate more on the presence of valuable minerals in the tertiary basin.